Public Transport Knowledge Management in Local Communities - et al., Pratya Nuankaew (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this research is to construct an application prototype from the study of public transport problems in the local communities of Thailand. There are three main goals for research to be successful: (1) To study problems and situations in which communities are affected by public transport. (2) To design and standardize the management of problems and situations in which the community is affected by public transport. (3) To construct a public transport application prototype for local communities of Thailand. Population and sampling were scoped from the public transport service provider in Phayao Province, Thailand. The prototype was constructed with an Android Mobile Application. The results of the study showed that the developed application prototypes showed a high level of satisfaction (total means is equal to 3.95, S.D. is equal to 0.73) with the design and implementation of the prototype. In the future, the researcher will bring the application to the test and deployment.